The effect of socio-demographic variables travel characteristics on motivation of Muslim family tourists in Malaysia - Yuhanis, Abdul Aziz; Siti Rahayu, Hussin; Nezakati, Hossein *; Raja Nerina, Raja Yusof; Haslinda, Hashim (Emerald, 2018)
Purpose This paper aims to investigate the socio-demographic variables that affect the motivation of Muslim tourists in Malaysia, and to examine the travel characteristics factors that affect the motivation in decision making of Muslim tourists travelling to Malaysia. Design/methodology/approach The study surveys questionnaires for data collection. Convenience sampling technique was used on the selected sample. The study was conducted in Malaysia, where the target respondents included Muslim family tourists with ages ranging from 18 to 64 years. Findings The findings show that motivation differs significantly among different levels of the socio-demographic characteristics except for gender and income. The result also reported that a majority of tourists’ travel behaviour was significantly different unless when it comes to seeking accommodation. Results also revealed a tendency for long holiday stays among Muslim tourists in Malaysia. Research limitations/implications In this study, the examination of motivation on the Muslim family tourists has provided significant influence in managing the family tourist experience. On the other hand, most previous studies have shown that motivation is positively guided by general “push and pull” factors. However, this research demonstrates that components such family financial income and age of respondents has an effect on Muslim family tourists’ motivation, thus justifying the experience effect. Practical implications It is crucial for the service provider and destination management organizations to differentiate their products and services so that the packages and experience will be more meaningful. Social implications Destination packages should be appropriately designed and positioned in the target markets to meet the needs and wants of different Muslim family groups. Communication should emphasize not only the most distinctive characteristics but also the most suitable holiday packages that the family tourist can afford to pay. This would assist the family in the decision-making process and choice processes and facilitate the family’s expectation. Originality/value This research paper related to Islamic tourism marketing which can be used to formulate appropriate marketing strategies, build a viable market segment and design practical marketing strategies to attract potential Muslims travellers.